Нормування розрахункових характеристик максимального стоку весняних водопіль і дощових паводків, заснованих на геометричних моделях їх гідрографів - Гопченко, Є. Д.; Романчук, М. Є.; Кирилюк, О. С. (Київський національний університет імені Тараса Шевченка, 2017)
Серед характеристик максимальному стоку дощовим паводкам і весняним водопіллям належить особливе місце, оскільки від їх розмірів залежить безпечність функціонування гідротехнічних споруд, населених пунктів, розміщення господарських об’єктів й інш. Нормативна база по характеристикам є недосконалою. Відсутність матеріалів спостережень за гідрологічним режимом, особливо схилового стоку, залишається свого роду гальмом при розробці надійних рекомендацій і їх застосуванню. У спеціальній літературі є досить багато посилань на окремі авторські дослідження максимального стоку річок. Щодо практичних застосувань, то вони обмежуються емпіричними структурами. Автори статті при обґрунтуванні робочого варіанту скористались моделями, віднесеними до геометричних одномодальних схем. Обмеженість даних по схиловому припливу сприяла дослідженням, які були використанні для вирішення поставлених завдань і розробці теоретичних положень. Рекомендації доведенні до рівня практичних застосувань і відкривають свого роду шляхи покращення як практичних, так і теоретичних можливостей.

The article substantiates the methodological basis for the valuation of the design characteristics of extremely high discharges of water spring flood and storm floods, which pose a great security for hydraulic structures and their use in river basins, as well as settlements. The scientific and methodological base is based on the use of the geometric structure of single-modal hydrographs of slope inflow and channel flow. In order to simplify the calculation scheme, hydrographs are considered in an extended time format, starting with the maximum water flow. This, in turn, contributes to a spatiotemporal generalization of the characteristics of both the inclined tributary and the hydrographs of channel flow. Among the characteristics of the maximum runoff of rain floods and spring falls is a special place, because of their size depends on the safety of the operation of hydraulic structures, settlements, the location of economic objects, and others. But it should be noted that the normative base on characteristics, including SNiP 2.01.14 83 [2], remains imperfect. The absence of observation materials for the hydrological regime, especially the sloping runoff, remains a kind of brake in developing reliable recommendations and their application. In the literature there are quite a few references to individual author studies of the maximum runoff of the rivers. As far as practical applications are concerned, they are limited to empirical structures. The authors of the article, when substantiating the working variant, used models subjected to geometric one-modal schemes. The limited data on the incline influences contributed to the research that was used to solve the problems and develop theoretical provisions. The recommendations are brought to the level of practical applications and open up a kind of ways to improve both practical and theoretical capabilities. Transformation modules maximum of slope influx in the channel network is described by the coefficient of transformation hydrographs of slope influx in to the channel network and coefficient of channel and floodplain regulation. A new universal model of high flow, which allows perform determination of the design characteristics of rain and spring floods regardless of their genesis and catchment areas are suggested.
Normalization of the calculated characteristics of the maximum runoff of spring water and rain floods, based on the geometric models of their hydrographs
Keywords: дощові паводки; весняні водопілля; максимальний стік; гідрографи; геометричні моделі за їх формою; rain floods; spring floods; maximum runoff; hydrographs; geometric models according to their form